Contribution of the method of diagnosis and the range of IgE –non IgE at cow’s milk allergy in daily practice (Annals of Medical Research, 2021)
Aim: It is aimed to evaluate the place of the diagnosis method in routine practice and the ISA patients range according to the types of immune reactions.